Resistência e conquista da terra a partir de Dt 26,5-11 - Ribeiro, Valdivino Souza (2002)
One can perceive very clearly how the historical development of Brasil is permeated by the history of mankind. Religion especially marks the struggles for survival, the conquest of the land, and better conditions for life. Indigenous people show how the relationship to the land is profound and logical like the relationship to the Creator. The African Negroes procured divine attunement and return to roots. The Canudos movement is a search for faithfulness to God's law in contrast to Satan's. In the land struggle and the equitable distribution of income, the CPT (Pastoral Land Commission) and the MST (Landless Peasant Movement) endeavour to make use of this mysticism. Religious motivation is always present in the movements of land resistance and conquest. Deut 26, 5-11 is a Biblical text that forms part of a larger whole: the feast of the first fruits, and signalizes that, even in an accumulative process, there exists a counter reaction. Such was the case with Hezechias and, especially, Josiah in their opposition to political and religious concentration. The Biblical text shows that the State didn't totally win the battle, for there are references to resistance that survive in the political-religious reform ceremony. In the modern era it is very opportune to read Deut 26,5-11 and sing popular community liberation hymns seeing that land and income continue to be monopolized. Liberation Hymns invite all to resist and take possession of the land. The struggle is all encompassing as should joy.